Genomic Insights Into the Archaea Inhabiting an Australian Radioactive Legacy Site - Vázquez-Campos, Xabier; Kinsela, Andrew S.; Bligh, Mark W.; Payne, Timothy E.; Wilkins, Marc R.; Waite, T. David (Frontiers in Microbiology, 2021)
During the 1960s, small quantities of radioactive materials were co-disposed with chemical waste at the Little Forest Legacy Site (LFLS, Sydney, Australia). The microbial function and population dynamics in a waste trench during a rainfall event have been previously investigated revealing a broad abundance of candidate and potentially undescribed taxa in this iron-rich, radionuclide-contaminated environment. Applying genome-based metagenomic methods, we recovered 37 refined archaeal MAGs, mainly from undescribed DPANN Archaea lineages without standing in nomenclature and ‘Candidatus Methanoperedenaceae’ (ANME-2D). Within the undescribed DPANN, the newly proposed orders ‘Ca. Gugararchaeales’, ‘Ca. Burarchaeales’ and ‘Ca. Anstonellales’, constitute distinct lineages with a more comprehensive central metabolism and anabolic capabilities within the ‘Ca. Micrarchaeota’ phylum compared to most other DPANN. The analysis of new and extant ‘Ca. Methanoperedens spp.’ MAGs suggests metal ions as the ancestral electron acceptors during the anaerobic oxidation of methane while the respiration of nitrate/nitrite via molybdopterin oxidoreductases would have been a secondary acquisition. The presence of genes for the biosynthesis of polyhydroxyalkanoates in most ‘Ca. Methanoperedens’ also appears to be a widespread characteristic of the genus for carbon accumulation. This work expands our knowledge about the roles of the Archaea at the LFLS, especially, DPANN Archaea and ‘Ca. Methanoperedens’, while exploring their diversity, uniqueness, potential role in elemental cycling, and evolutionary history.